Implementation-Specific Nutritional Interventions in Stunting Prevention: Literature Review - Yunita Maharani Dewi; Tina Shinta Parulian; Maria Yunita Indriarini (Faculty of Nursing, Universitas Jember, 2022)
Stunting is one of the nutritional problems in the world. Stunting is predicted to increase by 15% worldwide due to the pandemic. Specific nutritional interventions are one of the stunting prevention interventions carried out by the health sector that have been shown to reduce one-third of the prevalence of stunting in the world. The purpose of this paper is to get an overview of the implementation of specific nutritional intervention programs in stunting prevention in Indonesia. The article used in this literature review was published in 2012-2021. The databases used are PubMed and Google Scholar. Eleven selected articles for analysis. One article explained that the prevalence of stunting differs by region and the incidence is higher in eastern Indonesia. Two articles describe the specific nutritional intervention programs in Indonesia Six articles discuss the implementation of each program in specific nutritional interventions. Programs that have been running well are additional feeding, pregnant women, Initiation of Early Breastfeeding, breastfeeding, vitamin A and zinc administration. Poor implementation is exclusive breastfeeding and immunization. Two articles discussing the evaluation of the implementation of specific nutritional interventions in Indonesia are already good, the obstacles found are the lack of even spread of health workers. Researchers suggest that an evaluation is needed for the implementation of specific nutritional intervention programs.